Síntese e caracterização de nanopartículas de vidro bioativo contendo Ca e Mn e incorporação em hidrogéis injetáveis de Pluronic® F127 - Priscilla Mol Queiroz (2021)
Mesoporous bioactive glasses have shown great potential for tissue regeneration due to their ability to bind to the bone in physiological environment and to stimulate bone repair. The incorporation of different ions with specific therapeutic properties in the bioactive glass network is a strategy to improve the material performance for specific applications. Among the different ions with physiological activities, the manganese ions incorporation has shown to enhance biological responses by favoring osteogenic differentiation. In addition, aiming to obtain a biomaterial with improved properties in terms of application and performance, the incorporation of bioactive glass particles into injectable polymeric matrices allows for a minimally invasive application alternative directly to the place where the material is needed. In this work, different compositions of bioactive glass mesoporous nanoparticles containing manganese were produced to evaluate the Mn influence on the bioactive glass structure and properties. Morphological and structural analysis confirmed that spherical bioactive glass mesoporous nanoparticles were obtained. The Mn presence in the bioactive glass structure was verified, as well as the manganese oxides formation according to the Mn concentration used. In vitro results showed controlled ion release capacity and bioactivity in physiological medium. Cellular assays showed a manganese dose-dependent effect on cell viability and alkaline phosphatase activity. Finally, the bioactive glass nanoparticles were incorporated into a Pluronic® F-127 hydrogel to obtain a new nanocomposite. The material was evaluated for structural characterization, thermosensitive behavior and injection capacity. Hydrogels of up to 89 % porosity were obtained and rheological and injectability tests proved the material feasibility for a minimally invasive administration through syringes. Moreover, the bioactive glass nanoparticles addition improved the hydrogels elastic properties and stability at body temperature, showing an increase in the elasticity modulus (G’) and residence time, evaluated by a mass loss assay. Furthermore, the viscosity at low temperatures was not compromised by the bioactive glass incorporation, allowing a smooth injection and suitable gelation temperature and time for biomedical applications. Considering the obtained results, the produced nanocomposites have great potential for use as injectable devices for bone regeneration.